PENGEMBANGAN DAN ANALISIS SOAL ULANGAN KENAIKAN KELAS KIMIA SMA KELAS X BERDASARKAN CLASSICAL TEST THEORY DAN ITEM RESPONSE THEORY (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2011)
This research is title “Test Development and Analysis of First Grade Senior High School Final Examination in chemistry Based on Classical Test Theory and Item Response Theory”. This research is conducted to develop a standard test instrument for final examination in senior high school at first grade using analysis based on classical test theory and item response theory. The test is a multiple choice test which consists of 75 items. Each item has five options. The research method is research and development method to get a product of test items which fulfill item criterion such as validity, reliability, item discrimination, item difficulty and distracting options quality based on classical test theory and validity, reliability, item discrimination, item difficulty and pseudo-guessing based on item response theory. The three parameter item response theory model is used in this research. Research and development method is conducted until preliminary field test to 102 first grade students in senior high school. Based on the research result, the test fulfills criterion as a good instrument based on classical test theory and item response theory. The final examination test items have vary of item quality so that some of them need a revision to make them better either for the stem and the options. From the total of 75 test items, 21 test items are declined and 54 test items are accepted.